Treatment of Waste Whey by Solvent Sublation Method - Mukhopadhyay, Goutam; Sarkar, Aditya; Samanta, Manisha; Pal, Tripti; Chakraborty, Biswajit; Dutta, Chandrima; Roy, Abhinandan; Halder, Pijush; Dutta, Souhardya (Asian Journal of Pharmaceutical Research and Development, 2021)
Whey liquid is produced in large amounts all over the world every day, this liquid has a high biochemical oxygen demand due to which it creates a serious problem named pollution. But if the liquid is treated beforehand the problem can be overcome. While there are several conventional techniques to treat the liquid before dumping, still they are not as efficient as the solvent sublation method. However, this method is not widely studied yet for large-scale applications. In this study, our objective was to determine the effect of several factors which can alter this method’s efficiency e.g. pH, Gas flow rate, volumetric flow rate, the concentration of feed, etc. We discussed in which conditions the solvent sublation process will give its maximum efficiency. This study will not only help in wastewater treatment but also for the separation of molecules of interest from a solution.